2016
DOI: 10.11138/fneur/2016.31.2.095
|View full text |Cite
|
Sign up to set email alerts
|

Delayed auditory conduction in diabetes: is metformin-induced vitamin B12 deficiency responsible?

Abstract: SummaryThe present study aims to evaluate the functional integrity of the auditory pathway in patients with diabetes taking metformin. A further aim is to assess its association with vitamin B12 deficiency induced by metformin. Thirty diabetics taking metformin and 30 age-matched non-diabetic controls were enrolled. Stimulus-related potentials and vitamin B12 levels were evaluated in all the subjects. The diabetics showed deficient vitamin B12 levels and delayed wave III latency and III-V interpeak latency in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The aim of this study was to assess whether metformin is a risk factor for the development of DPN by evaluating the impact of metformin on the serum level of cobalamin and homocysteine in type 2 DM. Most of the past clinical studies demonstrated that metformin has some impact on plasma cobalamin and homocysteine and there are some case reports indicating deterioration of neuropathy with metformin 29 32 . Some recent researches have investigated the relation of metformin with the level of cobalamin and neuropathy with conflicting results 29 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to assess whether metformin is a risk factor for the development of DPN by evaluating the impact of metformin on the serum level of cobalamin and homocysteine in type 2 DM. Most of the past clinical studies demonstrated that metformin has some impact on plasma cobalamin and homocysteine and there are some case reports indicating deterioration of neuropathy with metformin 29 32 . Some recent researches have investigated the relation of metformin with the level of cobalamin and neuropathy with conflicting results 29 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%